2021
DOI: 10.1080/10428194.2021.1901090
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab plus gemcitabine and oxaliplatin (R-GemOx) in refractory/relapsed diffuse large B-cell lymphoma: a real-life study in patients ineligible for autologous stem-cell transplantation

Abstract: 2021): Rituximab plus gemcitabine and oxaliplatin (R-GemOx) in refractory/relapsed diffuse large B-cell lymphoma: a real-life study in patients ineligible for autologous stem-cell transplantation, Leukemia & Lymphoma,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 25 publications
(27 reference statements)
2
28
0
Order By: Relevance
“…This group was unlikely to receive curative‐intent salvage therapy and, as expected, their median OS was short, 4.9 months. Few clinical trials have targeted older patients but in a phase 2 study of transplant‐ineligible patients (median 72 years), Cazelles et al reported a median OS of 10 months following treatment with rituximab (R)‐GemOx 32 . In a randomized study comparing polatuzumab vedotin and R‐bendamustine against R‐bendamustine alone in patients 30–86 years old, median OS was 12.4 months in the experimental arm vs 4.7 months in the standard arm 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group was unlikely to receive curative‐intent salvage therapy and, as expected, their median OS was short, 4.9 months. Few clinical trials have targeted older patients but in a phase 2 study of transplant‐ineligible patients (median 72 years), Cazelles et al reported a median OS of 10 months following treatment with rituximab (R)‐GemOx 32 . In a randomized study comparing polatuzumab vedotin and R‐bendamustine against R‐bendamustine alone in patients 30–86 years old, median OS was 12.4 months in the experimental arm vs 4.7 months in the standard arm 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical trials have targeted older patients but in a phase 2 study of transplant-ineligible patients (median 72 years), Cazelles et al reported a median OS of 10 months following treatment with rituximab (R)-GemOx. 32 In a randomized study comparing polatuzumab vedotin and R-bendamustine against R-bendamustine alone in patients 30-86 years old, median OS was 12.4 months in the experimental arm vs 4.7 months in the standard arm. 15 In the recent ZUMA-7 22 and TRANSFORM 23 randomized phase 3 trials comparing CAR T products with standard second-line therapy for large B-cell lymphoma, subgroup analyses showed that CAR T was more efficacious than standard therapy for both elderly (aged ≥65) and younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…Due to retrospectivity and the out-patient setting additional unreported events cannot be completely excluded. However, compared with previous palliative regimens in R/R DLBCL patients ( 24 , 29 , 38 , 50 , 58 ) and given the seniority of the multiply pretreated cohort, the safety profile of TEPIP is tolerable and manageable. For instance, a phase 3 trial treating a similar patient population with pixantrone vs. comparator chemotherapy showed grade 3 or 4 toxicity in 76.5%vs 52.2% with neutropenia being the predominant event ( 50 ).…”
Section: Discussionmentioning
confidence: 98%
“…Remaining treatment options comprise conventional regimens with acceptable toxicity such as R-GemOx ( 23 , 24 ), R-DHAOx ( 25 ), as well as R-Bendamustin ( 26 ) improving OS especially in combination with the anti-CD79b drug-conjugate polatuzumab-vedotin ( 27 ). Further, monotherapies or combinations of novel targeted agents like bi-specific antibodies ( 28 ), ibrutinib ( 29 ) and lenalidomide in combination with rituximab ( 30 ) or the anti-CD19 antibody tafasitamab ( 31 ) have been approved recently or are undergoing evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with long-term survival in approximately half of patients with first relapse of DLBCL, and achieves superior OS (53 vs. 32%), overall response rate (ORR) (84 vs. 44%), and PFS (46 vs. 12%) compared with salvage therapy alone [21]. For patients unsuitable for autologous HCT, salvage treatments with rituximab combined with chemotherapy have a median OS and PFS of 10 and 6 months, respectively [22]. Other regimens in R/R DLBCL include polatuzumab-rituximab-bendamustine (median OS and PFS of 12 and 9 months) [23], tafasitamab-lenalidomide (median OS and PFS of 33 and 11 months) [24], and CAR T-cell therapies (ORR of 50-85% and CR of 47%) [25,26].…”
Section: Lymphoma: An Overviewmentioning
confidence: 99%